Respond to this Question
Similar Questions

math (7)
Find the secondorder partial derivatives of the function. f(x,y) = x^5 + x^2y + x + 5 a. fxx = ? b. fyy = ? c. fxy = ? d. fyx = ?
asked by Mia on April 30, 2014 
math (8)
Find the secondorder partial derivatives of the function. f(x,y) = x^5 + x^2y^2 + y^4 + x + y a. fxx = ? b. fyy = ? c. fxy = ? d. fyx = ?
asked by Mia on April 30, 2014 
Calculus
Find the four second partial derivatives and evaluate each at the given point. Function f(x, y) = x^3 + 2xy^3 − 9y Point (9, 2) fxx(9, 2) = fxy(9, 2) = fyx(9, 2) = fyy(9, 2) =
asked by Calculus Help on November 17, 2015 
calculus
find the secondorder partial derivatives of f(x,y)=x^3 + x^2y^2 + y^3 + x+y and show that the mixed partial derivatives fxy and fyx are equal
asked by maggie on March 7, 2012 
Calculus
f(x, y) = 3ycos x, 0 ≤ x ≤ 2π Finding the locla minima, maxima, and saddle points. Having difficulty as so far I have: Fx = 3ysinx Fy = 3cosx Fxx = 3ycosx Fyy = 0 Fxy = 3sinx I have set both Fx and Fy equal to 0 but am not
asked by OscarEE on October 19, 2016 
Maths
Can someone help me with the following? Prove that (grad)^2 f(r) = D^2/dr^2 + (2/r) Df/Dr Where D^2/dr^2 refers to the second partial derivative of f , w.r.t. r and Df/ Dr refers to partial derivative of f, w.r.t r vector r = xi +
asked by Aryaa on October 28, 2019 
Math
Given that f(x,y)=xy/(x^2+y^2), hence show that fxy=fyx
asked by Beta plus on October 20, 2009 
Math
Given that f(x,y)=xy/x^2+y^2, hence show that fxy=fyx
asked by Beta plus on October 20, 2009 
Calculus III
Hi, this question is about Langrange multipliers. Given f(x,y) = y^2  x^2, subject to the constraint g(x,y) = 0.25x^2 + y^2 = 1, find the max and mins. So I found the partial derivatives for both f(x,y) and g(x,y): fx = 2x fy =
asked by Justin on December 10, 2016 
Calculus III
Hi, this question is about Langrange multipliers. Given f(x,y) = y^2  x^2, subject to the constraint g(x,y) = 0.25x^2 + y^2 = 1, find the max and mins. So I found the partial derivatives for both f(x,y) and g(x,y): fx = 2x fy =
asked by Justin on December 9, 2016